2018
DOI: 10.17770/sie2018vol1.3229
|View full text |Cite
|
Sign up to set email alerts
|

Modular Approach to Teaching and Learning English Grammar in Technical Universities

Abstract: The aim of this research is to find out the effectiveness of a modular approach in teaching and learning to assess students’ performance, achievement and motivation and to decide if a modular approach is more effective than traditional methods while performing an experiment with two groups of students learning English at a technical university. The researchers consider a modular specification to be a technology in which the content is divided into a number of units or modules, each of which is examined separat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 2 publications
(2 reference statements)
2
13
1
Order By: Relevance
“…Modules were usually also equipped with evaluation instruments so that students could find out how far they mastered the lecture material. Furthermore, through the module, lecturers can choose the core material that will be presented later and limit the material so that students can understand it more easily (Ibyatova, Oparina & Rakova, 2018;Coman et al, 2020). However, this study's results contradict the research results by Fatani (2020) & Shahzad (2021, which concluded that students preferred video conferencing as their lecture material.…”
Section: Student Perceptions Of the Types Of Online Lecture Materialscontrasting
confidence: 72%
“…Modules were usually also equipped with evaluation instruments so that students could find out how far they mastered the lecture material. Furthermore, through the module, lecturers can choose the core material that will be presented later and limit the material so that students can understand it more easily (Ibyatova, Oparina & Rakova, 2018;Coman et al, 2020). However, this study's results contradict the research results by Fatani (2020) & Shahzad (2021, which concluded that students preferred video conferencing as their lecture material.…”
Section: Student Perceptions Of the Types Of Online Lecture Materialscontrasting
confidence: 72%
“…"Structured Module vs. Self-Paced Modular Approach in Teaching Trigonometry" by Rodin M Paspasan (2015). based on the result it showed that self-passed modular approach helped them also improved their level of performance in relation to plane trigonometry and regardless of their mathematical abilities compared to the structured approach Ibyatova, Oparina, and Rakova (2018). on "Modular Approach to Teaching and Learning English Grammar in Technical University", the result of their study entitled "Modular Approach to Teaching and Learning English Grammar in Technical University"…”
mentioning
confidence: 99%
“…The results showed that the participants believed that the modular curriculum was more fruitful than the traditional system, and it could be revised to increase its effectiveness. In a study with similar positive results, Ibyatova et al (2018) aimed to assess the effectiveness of a modular system on students' performance, achievement, and motivation, in comparison with the traditional system. They concluded that modular syllabuses were valuable and motivating and helped students follow the course, although improvements were needed.…”
Section: Modular Systemmentioning
confidence: 99%